Genomic epidemiology and characterisation of penicillin-sensitive Staphylococcus aureus isolates from invasive bloodstream infections in China: an increasing prevalence and higher diversity in genetic typing be revealed. Issue 1 (31st December 2022) - Jin, Ye; Zhou, Wangxiao; Zhan, Qing; Chen, Yunbo; Luo, Qixia; Shen, Ping; Xiao, Yonghong
ABSTRACT: Many countries have reported increasing rates of penicillin-susceptible methicillin-sensitive Staphylococcus aureus (MSSA-PEN S ). To date, there is relatively little known about the current situation and molecular characteristics of MSSA-PEN S in China. In this study, we carried out a laboratory-based multi-region retrospective study to investigate the genomic epidemiology and characterisation of MSSA-PEN S isolated from invasive bloodstream infections (BSIs) across 17 provinces. The prevalence of MSSA-PEN S isolates increased significantly over the 6-year period, with the proportion increasing from 3.51% in 2014–8.80% in 2019, an average relative increase of 22.14% per year (95% confidence interval 9.67%-34.61%, P for trend <0.001), suggesting that China is experiencing a resurgence of MSSA-PEN S . Phylogenetic analysis showed a higher strain diversity occurred; the most frequent clonal complexes (CCs) identified were CC188 (17.14%), CC398 (15.71%) and CC5 (15.71%). Over half of MSSA-PEN S strains were pan-susceptible, with erythromycin the most frequent resistance observed. Moreover, 25 isolates were identified as immune evasion cluster negative, including CC15, CC188 and CC1, and 6 strains encoded the Panton-Valentine leucocidin gene. Importantly, virulence assays showed that MSSA-PEN S exhibited a level of virulence comparable to that of penicillin-resistant MSSA (MSSA-PEN R ), indicating that more-sensitive strains should not be mistaken for lacking aggressiveness in vivo . Furthermore, 11 of these isolates were confirmed as blaZ positive but phenotype sensitive, with different amino acid changes in blaZ . Our data support the recommendation to clinicians regarding the usage of penicillin in invasive BSIs caused by MSSA-PEN S, which might create a novel opportunity for better antimicrobial stewardship in the future.